METHODOLOGY OF USING TELECOMMUNICATION STUDY PROJECTS IN INDEPENDENT EDUCATION - Ashurova , Laylo (Educational Research in Universal Sciences, 2023)
The article highlights the essence and content of educational telecommunication projects, and the requirements for the effective organization of telecommunication projects in the field of pedagogy are based on. The procedure for organizing the defense of the educational project and external evaluation is presented. “Safety techniques in the use of information and communication system technical means” from the subject of “Labor protection and safety techniques” are based on the purpose, design and activity tasks and pedagogical tasks of the educational project of telecommunications. The typology and stages of the educational project have been developed.